Biological Evaluation of Isosteric Applicability of 1,3‐Substituted Cuneanes as m‐Substituted Benzenes Enabled by Selective Isomerization of 1,4‐Substituted Cubanes - Fujiwara, Kan; Nagasawa, Shota; Maeyama, Ryusei; Segawa, Ryosuke; Hirasawa, Noriyasu; Hirokawa, Takatsugu; Iwabuchi, Yoshiharu (Chemistry : a European journal, 2024)
We herein evaluate a biological applicability of 1,3‐substituted cuneanes as an isostere of m‐substituted benzenes based on its structural similarity. An investigation of a method to obtain 1,3‐substituted cuneanes by selective isomerization of 1,4‐substituted cubanes enables this attempt by giving a key synthetic step to obtain a cuneane analogs of pharmaceuticals having m‐substituted benzene moiety. Biological evaluation of the synthesized analogs and in silico study of the obtained result revealed a potential usage of cuneane skeleton in medicinal chemistry. Biological evaluation of cuneane analogs of ketoprofen, an anti‐inflammatory drug having m‐substituted benzene moiety, was conducted. This study was inspired from the structural similarity of 1,3‐substituted cuneanes with m‐substituted benzene. Selective isomerization of 1,4‐substituted cubanes into 1,3‐substituted cuneanes enabled this evaluation. Biological evaluation of the synthesized analogs of ketoprofen and in silico study of the result of biological study revealed a potential isosteric usage of cuneane skeleton as a m‐substituted benzenes in medicinal chemistry.